Macro-nutrient and hydrological trends in some streams of the Waterberg, Limpopo: investigating the effects of land-use change on catchment water quality - Burne, Craig (My University, 2016)
South Africa is faced with water quantity and quality issues in most catchments. Intensification of coal-based industrial activity in the Waterberg, Limpopo and the concomitant emissions of oxides of nitrogen (NOX) and sulphur (SOX) pose potential ecological impacts to regional freshwater systems. Some research indicates that a significant proportion of minerals in the Waterberg parent rock may be prone to acid generation with catchment soils being potentially susceptible to acidification via NOX and SOX deposition. Cultural and recurrent nutrient loading of freshwater bodies also impacts on primary production and can ultimately alter the natural structure and functioning of these ecosystems. Trend analyses on historical hydrological data from 1982 to 2013 were carried out for several response water quality variables from six quaternary Waterberg catchments. Results were assessed for possible changes attributable to increased NOX and SOX loading post commencement of large-scale coal combustion. Historical inorganic N:P ratios were calculated in conjunction with a series of nutrient (N and P) bioassay experiments to predict which nutrient may be limiting growth of stream periphyton. Although trends were identified in most catchments for several of the water quality variables, the notion that the onset of large scale coal combustion has led to noticeable downward trends in pH and upward trends in either inorganic N or sulphate is not unequivocal. Patterns in trends were not distinct for catchments situated in close proximity to the primary emission source and those further away. Nor were there any distinct differences in trends between upwind and downwind catchments. Climate and geo-hydrological factors are likely to still function as the primary drivers of spatial and temporal variation in past and present catchment water quality. Contrary to the view that stream primary production is limited largely by the availability of P, predictions based on N:P ratios calculated in this study suggest N to be the limiting nutrient. This was shown to be the case in four of the five study-site rivers. N-limitation increased by 18% (67% to 85%) in the Matlabas River post-commencement of large-scale coal combustion. A greater increase of 24% (60% to 84%) was observed in the Middle Mokolo. Although cultural eutrophication levels in the Waterberg do not yet exceed management-set targets, the cumulative effect of industrial-derived nutrient inputs remains a threat to the nearshore marine ecosystem and human communities living downstream.
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for the degree of Master of Science November 2015, Johannesburg
Keywords: Rivers.; Hydrology.; Water quality.